Hubungan antara Kompensasi dengan Komitmen Organisasi Guru Sekolah Menengah Pertama Swasta di Kecamatan Pulo Gadung - Tri Sulistyo Jati Mukarrom; Neti Karnati; Winda Dewi Listyasari (Universitas Negeri Jakarta, 2017)
This study aims to determine the relationship between compensation and organizational commitment junior high school teachers in the district Pulo Gadung. The research approach is a quantitative approach to the method used survey methods. This study uses correlational study analysis. The study population was Junior highschool teachers in the district Pulo Gadung with the sample amounted to 79 teachers. Sampling was done randomly by using simple random sampling with data collection using the questionnaire. It can be concluded that there is a relationship between compensation and organizational commitment. This means that the higher the compensation it will further enhance the organization's commitment junior high school teachers in the district Pulo Gadung.